Pengaruh Pengungkapan Corporate Social Responsibility, Return On Assets, dan Debt to Equity Ratio terhadap Price To Book Value - Reza Kiki Wahyudin; Nurhayati (Bandung Conference Series: Accountancy, 2024)
Abstract. This research aims to determine the effect of Corporate Social Responsibility Disclosure, Return On Assets, Debt to Equity Ratio on Price to Book Value. The unit of analysis in this research is non-primary consumer goods companies in the consumer services subsector listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. Sampling was taken using purposive sampling technique to obtain a sample of 31 companies. The data that can be obtained in this research is 124 data results from many samples multiplied by the period. The analytical method for this research uses multiple linear regression with panel data assisted by the Eviews 12 application program. Simultaneously, the results of this research show that Disclosure of Corporate Social Responsibility, Return On Assets, Debt to Equity Ratio have a significant effect on Price to Book Value. Partially, the results of this research show that Corporate Social Responsibility Disclosure has a positive and significant effect on Price to Book Value. Return On Assets has a positive and significant effect on Price Book Value. Debt to Equity Ratio has a negative and significant effect on Price Book Value. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Pengungkapan Corporate Social Responsibility, Return On Assets, Debt to Equity Ratio terhadap Price to Book Value. Unit analisis dalam penelitian ini adalah perusahaan barang konsumen non-primer subssektor jasa konsumen yang terdaftar di Bursa Efek Indonesia (BEI) periode 2019-2022. Pengambilan sampel dengan menggunakan teknik purposive sampling sehingga diperoleh sampel sebanyak 31 perusahaan. Data yang dapat diperoleh dalam penelitian ini sebanyak 124 selama empat tahun. Metode analisis penelitian ini menggunakan regresi linear berganda dengan data panel dibantu oleh program aplikasi Eviews 12. Secara simultan, hasil penelitian ini menunjukkan bahwa Pengungkapan Corporate Social Responsibility, Return On Assets, Debt to Equity Ratio berpengaruh signifikan terhadap Price to Book Value. Secara parsial, hasil penelitian ini menunjukkan bahwa Pengungkapan Corporate Social Responsibility berpengaruh positif dan signifikan terhadap Price to Book Value. Return On Assets berpengaruh positif dan signifikan terhadap Price Book Value. Debt to Equity Ratio berpengaruh negatif dan signifikan terhadap Price Book Value.